Hubungan Tingkat Pengetahuan Ibu Tentang Remaja Dengan Prestasi Akademik Mahasiswa Diploma III Keperawatan Jakarta - IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
The biggest demand experienced by adolescents is related to his success in the academic field. The success of adolescents in overcoming difficulties related to demands from inside and outside is greatly influenced by adolescent personal maturity. Adolescents who live in families that are able to meet biological, psychological, and social needs will grow and develop healthily, can actualize the potential they have and can learn in solving problems and the tasks they face, including tasks related to academics. The design in this research is descriptive analytic design with cross sectional research approach. The sampling method used in this study was to use purposive sampling, a sample of 98 person mothers. This study uses a chi-square test with an alpha value <0.05. The results found that the P Value value of 0.47 is greater than 0.05 so that the results of this study have no relationship between the level of mother's knowledge of adolescents on academic achievement. Recommendations for further research on the factors of adolescent success in academic achievement.